The Geo-imaginaries of potential in Mexico's Burgos Basin. (October 2021) - Fry, Matthew; Murphy, Trey
Abstract: In this paper, we use the geo-imaginary analytic to show how actors utilized narratives of resource potential and speculative economic futures for the Burgos Basin in northeastern Mexico to affect a broader liberalization of the nation's hydrocarbon sector. Our research traces the history of the word "potential" as a discrete and repetitive rhetorical technique used variously to speculate on hydrocarbon production, economic development, regional energy development, and risks associated with the Burgos. We also identify an array of visualizations, what we refer to as 'conjurings, ' used with narratives of potential to encourage investments in the Basin's development. These include: maps depicting Burgos geologic continuity with productive Texas fields, quantitative forecasts of growing production, visual depictions of private firms facilitating future production, and fracking as a necessary wedge to pry open the Burgos' unrealized potential. Finally, using governmentality, we link Burgos potentiality discourses to socio-political outcomes, including in the early 2000s, when the Basin was imagined as a way to counterbalance the skyrocketing costs of imported natural gas, continuing with the 2013–2014 Reforms, and into the post-Reform oil and gas conference spaces that facilitated financial investing opportunities. We also argue that the current administration leveraged anti-fracking discourse to reverse the liberalization of Mexico's hydrocarbon sector. By drawing together overlapping elements from scholarship into resources, speculation, and governmentality, and by parsing the ways that potential narratives and conjuring tools are deployed, this research contributes to ongoing debates in political geography around natural resources and the geopolitics of the subsurface. Highlights: Speculative narratives of resource potential are powerful at attracting finance and stimulating investments. We trace the empirics of "potential" narratives and visualizations used to hype futures for Mexico's Burgos Basin. Geo-imaginaries link discursive techniques and speculative tools to governmentality outcomes. We contend that Burgos geo-imaginaries were fundamental to rewriting and liberalizing Mexico's hydrocarbon governance.